PEMANFAATAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS NEGERI 12 SAROLANGUN - Nurul Atika; M. Syahran Jailani; Madyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the utilization of audio-visual media in improving students’ critical thinking skills in Islamic Religious Education at State Senior High School 12 Sarolangun. The research was motivated by the relatively low level of students’ critical thinking ability, which was influenced by limited and less optimal use of technology-based learning media in classroom instruction. The objective of this study was to analyze how audio-visual media are implemented in learning, how they contribute to the development of critical thinking skills, and what supporting and inhibiting factors influence their use. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, documentation, and triangulation involving the principal, vice principal, teachers, and students. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that the use of audio-visual media in Islamic Religious Education has not yet been fully optimized, although planning has been conducted systematically. Several challenges were identified, including differences in students’ characteristics, classroom management constraints, and limited student engagement. Efforts to address these challenges include combining audio-visual media with appropriate teaching methods, encouraging student participation, providing feedback and appreciation, and creating a positive learning environment. Properly managed, audio-visual media have strong potential to enhance students’ critical thinking skills and improve the effectiveness of the learning process.